City Strunggle: Rural and Urban Cultural Space in Bali In the Modern Indonesian Poetry of the 1960s—2012 (e-Journal of Linguistics, 2020)
This research is based on the space discourse that represents the cityand its environment in modern Indonesian literature in Bali in the1960s—2012. City and Bali are presented as a setting of events throughspace that shows the city as a social configuration of its people. Theresearch problem formulation is (1) rural and urban concepts in theappearance of tourist cities in Bali and (2) decentering Bali and Bali'schanges in the poems of the 1960s—2012. The data collection of thisresearch used the library method with note taking technique.Descriptive analytic analysis is used as a method with criticalinterpretive techniques. To analyze the data Derrida's deconstructiontheory was used, specifically decentering the rural and urban culturalparadigm which places the text as a social construction. The results anddiscussion of this research show that, first, poems of Balinese poetshave a tendency not to place cities as spaces as centers of progress, butcities that show individual awareness in the middle of the city. Second,decentering Bali is a hierarchical struggle that places rural and urbanculture as a contradiction of urban spatial policy with the efforts of thecommunity to defend its culture. Therefore, the poems of the 1960s— 2012 about Bali was a battle of discourses that put the binary oppositionto form because of the concept of rural and urban areas.
Keywords: Rhyme; city; rural and urban; Bali; decentering